Engineering Anion Resin based Amorphous Molybdenum Sulphide Composite for Treatment of Authentic Acid Mine Drainage. Issue 5 (October 2020) - Fu, Weng; Ji, Guozhao; Chen, Huihuang; Yang, Siyuan; Yang, Hong; Guo, Bao; Huang, Zhiqiang
Graphical abstract: Abstract: Acid mine drainage (AMD) is an acidic effluent containing many toxic heavy metal ions (e.g. Cu 2+, Cd 2+, Hg 2+ ) in mining industry, leading to serious environmental issues such as natural soil and aquatic pollution that threats the whole ecosystem and biosafety. Conventional neutralization and precipitation process cannot effectively remove heavy metal ions due to the risk of secondary contamination. Herein, we report an engineered amorphous molybdenum sulphide composite for selective removal of heavy metal ions from other co-existing ions in AMD solution. This composite was prepared by a facile ion exchange reaction, in which tetrathiomolybdate (MoS4 2- ) anions are firmly bonded to strong anion exchange resins by replacing chloride ions. The obtained composite was used to remove heavy metal ions from both synthetic and authentic AMD solution. The results of batch and fixed-bed column tests suggest high selectivity towards heavy metals, fast adsorption kinetics, good reusability and excellent adsorption capacities in the order of Hg(II)>>Pb(II)>Cu(II)>Cd(II). The adsorption data are fitted well by Langmuir model, indicating the single-layer adsorption mechanism. The theoretical adsorption capacities calculated by Langmuir model are 259.0 mg/g for Cu(II), 204.1 mg/g for Cd(II), 495.0 mg/g for Pb(II) and 1538.4 mg/g for Hg(II). The interaction between metal ions (Cu, Cd, Pb, Hg) and MoS4 2- anions are demonstrated by the formation of Mo-S-metal (Cu, Cd, Pb, Hg) bonding (the red shift of S2p peak in XPS spectra). Our results support the potential practical application of this new material for scavenging heavy metal ions in AMD wastewater.